The Correlation Between Demographic Characteristics With Wash Practices In Stunting Locus - Salsabila Nabilla Puspa Ilham; Laili Rahayuwati; Witdiawati Witdiawati; Iqbal Pramukti; Gusgus Ghraha Ramdhanie (Universitas Padjadjaran, 2023)
Human factors are very complex in the spread of disease. Stunting is caused by chronic malnutrition and infections in toddlers. Lack of access to clean water, hygiene, and sanitation contributes to stunting. Demographic factors can affect a person’s motivation to maintain hygiene. This study aims to be determined the correlation between demographic characteristics and water, sanitation, and hygiene (WASH) practices at the stunting locus. The method in this study used a correlational quantitative method with a cross-sectional design to be measured demographic characteristic and WASH practices variables. The study population consisted of Sukamulya village residents, and 463 Sukamulya village residents were sampled using total sampling. SPSS Version 26 for Windows was used for univariate and bivariate Chi-Square analysis. The results showed that 228 (49.2%) out of 463 of respondents had poor WASH practices. The results of the correlation test showed that there was a correlation between level of education and WASH practices with a score of Chi-Square 17,564 (p-value = 0,002). There is a correlation between education level and WASH practices at the stunting locus. Education affects a person’s perspective and decision-making, including environmental hygiene and health. Thus, the government and policymakers should hold WASH programs to educate the public about keeping the stunting locus clean.